A novel phantom and procedure providing submillimeter accuracy in daily QA tests of accelerators used for stereotactic radiosurgery*. (8th July 2016) - Brezovich, Ivan A.; Popple, Richard A.; Duan, Jun; Shen, Sui; Wu, Xingen; Benhabib, Sidi; Huang, Mi; Cardan, Rex A.
Abstract : Stereotactic radiosurgery (SRS) places great demands on spatial accuracy. Steel BBs used as markers in quality assurance (QA) phantoms are clearly visible in MV and planar kV images, but artifacts compromise cone‐beam CT (CBCT) isocenter localization. The purpose of this work was to develop a QA phantom for measuring with sub‐mm accuracy isocenter congruence of planar kV, MV, and CBCT imaging systems and to design a practical QA procedure that includes daily Winston‐Lutz (WL) tests and does not require computer aid. The salient feature of the phantom (Universal Alignment Ball (UAB)) is a novel marker for precisely localizing isocenters of CBCT, planar kV, and MV beams. It consists of a 25.4 mm diameter sphere of polymethylmetacrylate (PMMA) containing a concentric 6.35 mm diameter tungsten carbide ball. The large density difference between PMMA and the polystyrene foam in which the PMMA sphere is embedded yields a sharp image of the sphere for accurate CBCT registration. The tungsten carbide ball serves in finding isocenter in planar kV and MV images and in doing WL tests. With the aid of the UAB, CBCT isocenter was located within 0.10 ± 0.05 mm of its true positon, and MV isocenter was pinpointed in planar images to within 0.06 ± 0.04 mm . In clinical morning QA tests extending over an 18 months period the UAB consistently yielded measurements with sub‐mm accuracy. The average distance between isocenter defined by orthogonal kV images and CBCT measured 0.16 ± 0.12 mm . In WL tests the central ray of anterior beams defined by a 1.5 × 1.5 cm 2 MLC field agreed with CBCT isocenter within 0.03 ± 0.14 mm in the lateral direction and within 0.10 ± 0.19 mm in the longitudinal direction. Lateral MV beams approached CBCT isocenter within 0.00 ± 0.11 mm in the vertical direction and within ‐ 0.14 ± 0.15 mm longitudinally. It took therapists about 10 min to do the tests. The novel QA phantom allows pinpointing CBCT and MV isocenter positions to better than 0.2 mm, using visual image registration. Under CBCT guidance, MLC‐defined beams are deliverable with sub‐mm spatial accuracy. The QA procedure is practical for daily tests by therapists. PACS number(s): 87.53.Ly, 87.56.Fc